2023
DOI: 10.1172/jci164486
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors mitigate kidney tubular metabolic and mTORC1 perturbations in youth-onset type 2 diabetes

Abstract: RenalytixAI, Travere, Regeneron, IONIS, consulting fees through the University of Michigan from Astellas, Poxel, Janssen and UCB. In addition, M.K. has a patent PCT/EP2014/073413 "Biomarkers and methods for progression prediction for chronic kidney disease" licensed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Not all of the Schaub et al study findings fit neatly within the paradigm of receptor-mediated SGLT2 inhibition ( 18 ). Suppression of mTORC1 by lowered intracellular glucose and activation of AMPK may also reduce glycolysis ( 19 ).…”
Section: Putative Non-receptor-mediated Effects Of Sglt2 Inhibitionmentioning
confidence: 93%
See 3 more Smart Citations
“…Not all of the Schaub et al study findings fit neatly within the paradigm of receptor-mediated SGLT2 inhibition ( 18 ). Suppression of mTORC1 by lowered intracellular glucose and activation of AMPK may also reduce glycolysis ( 19 ).…”
Section: Putative Non-receptor-mediated Effects Of Sglt2 Inhibitionmentioning
confidence: 93%
“…In this issue of the JCI , Schaub et al describe changes in single-cell transcriptomics among young people with type 2 diabetes who were SGLT2 inhibitor users compared with nonusers and healthy controls ( 18 ). Although the comparison groups were small ( n = 6–10 each) and SGLT2 inhibitors were prescribed for clinical indications, the study observations provide detailed molecular information at the cellular level in the human kidney according to diabetes status and SGLT2 inhibitor use.…”
Section: Receptor-mediated Sglt2 Inhibition May Shift Energy Requirem...mentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of phosphate on glycolysis did not result in systemic changes in expression of metabolism genes. It is notable that another recent study of the effect of SGLT2 inhibitors in type I diabetes confirmed inhibition of glycolysis as one of the metabolic effects on kidney cells [28]. The investigators did not examine the effects on phosphate transport explicitly as the focus of this study was on metabolism.…”
Section: Andandmentioning
confidence: 99%